Packaging design training to increase the selling of dragon fruit crackers products in Batuah Village - Royke Vincentius Febriyana; Dwi Cahyadi; Ratna Wulaningrum; Rahmat Rahmat (Community Empowerment, 2021)
The abundantly harvested dragon fruit has encouraged the people at Batuah Village to make secondary product, in order to avoiding loss because the fruit is rotten, such as the dragon fruit crackers. Nowdays, the product has already marketed in the Mercure-Ibis Samarinda hotel chain. For the purpose it is considered important for the products to have good packaging. Therefore, the community service team do the coaching on how to make basic packaging design. The coaching trainee is taught on how to make packaging design from existed packaging pattern and then adjust it to the size of their products. The trainee was also taught on how to make simple design with design software. The results are that the trainee can make packaging design which the design and size are already adjusted with their product’s needs.